Studies of gallium nitride high electron mobility transistors (HEMTs) - Tie, Keven Guo Sheng (Nanyang Technological University, 2022)
Gallium Nitride (GaN) is a Group III/V wide bandgap nitride-based material that offer many unique properties. It not only offers higher breakdown strength, faster switching speed and lower on resistance, it significantly outperforms the traditional silicon-based device. These properties have been attracting attention of many engineering scientist and leaders of the commercial semiconductor industry. Also, with its properties, GaN is set to be in the forefront material in both existing and new applications. In recent times, many breakthroughs have been made in producing powerful GaN devices that are never seen in market before because of its wide spectrum of applications. In this report, GaN HEMTs will be further pushed to limits that are never seen before, namely introduction of new materials to the fabrication process, focusing on its compatibility to meet RF technology. Some transistors that are fabricated will be tested and analysed of its performance.